The effects of dietary organic selenium on growth, body composition and hematological parameters of common Carp (Cyprinus carpio) reared in recirculating aquaculture system: Effects of selenium on common Carp - Abdulrahman Mustafa, Ibrahim; Sofy Omar, Samad (Cellular and Molecular Biology, 2024)
A feeding trial was conducted to examine the effects of different levels of dietary organic selenium (Se) on the growth, body composition, and hematological indices of common carp. Se element was supplemented to the basal diet at the rates of 0.0, 0.5, 1 and 2 mgkg-1. Fish were randomly stocked at a rate of 25 fish into 500L tanks in the Recirculating Aquaculture System (RAS) system for 10 weeks. Weight gain, final body weight, and specific growth rate were significantly higher (p<0.05) in fish fed 0.5 mgkg-1 followed by 1 and 2 mgkg-1 treatment diets fish. The lowest growth rate values were detected in fish-fed basal diets. Feed consumption of fish fed Se was not significantly different (p>0.05), also the survival rate was similar among the treatment groups. Whole-body composition showed that fish fed 1 mgkg-1 had significantly higher (p<0.05) body moisture and protein as dry weight basis. The highest fiber content was in fish fed 2 mgkg-1, but ash was significantly higher in fish fed only 0.5 mgkg-1 and fat remained unaffected. Whole-body Se concentrations were significantly (p<0.05) increased with increasing Se levels in test diets. the red blood cells and hemoglobin were significantly higher (p<0.05) in fish fed only 0.5mgkg-1 and the basal diet. The white blood cells increased in fish fed the basal and 2 mgkg-1 diet, but the lymphocyte percentage was increased (p<0.05) in fish fed basal and 0.5 mgkg-1. The study concludes that dietary Se has an overall positive effect on common carp. Growth performance, protein content in fish body, selenium deposition and some hematological parameters were observed in fish fed dietary organic selenium specifically in fish fed 0.5 and 1 mgkg-1. Therefore, inclusion of Se in the diet from 0.5 to 1 mgkg-1 would be an optimal level for common carp feed.